Transcranial focused ultrasound stimulation of motor cortical areas in freely-moving awake rats - Wonhye Lee; Phillip Croce; Ryan W. Margolin; Amanda Cammalleri; Kyungho Yoon; Seung-Schik Yoo (BMC Neuroscience, 2018)
Abstract Background Low-intensity transcranial focused ultrasound (tFUS) has emerged as a new non-invasive modality of brain stimulation with the potential for high spatial selectivity and penetration depth. Anesthesia is typically applied in animal-based tFUS brain stimulation models; however, the type and depth of anesthesia are known to introduce variability in responsiveness to the stimulation. Therefore, the ability to conduct sonication experiments on awake small animals, such as rats, is warranted to avoid confounding effects of anesthesia. Results We developed a miniature tFUS headgear, operating at 600 kHz, which can be attached to the skull of Sprague–Dawley rats through an implanted pedestal, allowing the ultrasound to be transcranially delivered to motor cortical areas of unanesthetized freely-moving rats. Video recordings were obtained to monitor physical responses from the rat during acoustic brain stimulation. The stimulation elicited body movements from various areas, such as the tail, limbs, and whiskers. Movement of the head, including chewing behavior, was also observed. When compared to the light ketamine/xylazine and isoflurane anesthetic conditions, the response rate increased while the latency to stimulation decreased in the awake condition. The individual variability in response rates was smaller during the awake condition compared to the anesthetic conditions. Our analysis of latency distribution of responses also suggested possible presence of acoustic startle responses mixed with stimulation-related physical movement. Post-tFUS monitoring of animal behaviors and histological analysis performed on the brain did not reveal any abnormalities after the repeated tFUS sessions. Conclusions The wearable miniature tFUS configuration allowed for the stimulation of motor cortical areas in rats and elicited sonication-related movements under both awake and anesthetized conditions. The awake condition yielded diverse physical responses compared to those reported in existing literatures. The ability to conduct an experiment in freely-moving awake animals can be gainfully used to investigate the effects of acoustic neuromodulation free from the confounding effects of anesthesia, thus, may serve as a translational platform to large animals and humans.